Contrasting Roles for C/EBPα and Notch in Irradiation‐Induced Multipotent Hematopoietic Progenitor Cell Defects. (April 2015) - Fleenor, Courtney Jo; Rozhok, Andrii Ivan; Zaberezhnyy, Vadym; Mathew, Divij; Kim, Jihye; Tan, Aik‐Choon; Bernstein, Irwin David; DeGregori, James
Abstract: Ionizing radiation (IR) is associated with reduced hematopoietic function and increased risk of hematopoietic malignancies, although the mechanisms behind these relationships remain poorly understood. Both effects of IR have been commonly attributed to the direct induction of DNA mutations, but evidence supporting these hypotheses is largely lacking. Here we demonstrate that IR causes long‐term, somatically heritable, cell‐intrinsic reductions in hematopoietic stem cell (HSC) and multipotent hematopoietic progenitor cell (mHPC) self‐renewal that are mediated by C/EBPα and reversed by Notch. mHPC from previously irradiated (>9 weeks prior), homeostatically restored mice exhibit gene expression profiles consistent with their precocious differentiation phenotype, including decreased expression of HSC‐specific genes and increased expression of myeloid program genes (including C/EBPα). These gene expression changes are reversed by ligand‐mediated activation of Notch. Loss of C/EBPα expression is selected for within previously irradiated HSC and mHPC pools and is associated with reversal of IR‐dependent precocious differentiation and restoration of self‐renewal. Remarkably, restoration of mHPC self‐renewal by ligand‐mediated activation of Notch prevents selection for C/EBPα loss of function in previously irradiated mHPC pools. We propose that environmental insults prompt HSC to initiate a program limiting their self‐renewal, leading to loss of the damaged HSC from the pool while allowing this HSC to temporarily contribute to differentiated cell pools. This "programmed mediocrity" is advantageous for the sporadic genotoxic insults animals have evolved to deal with but becomes tumor promoting when the entire HSC compartment is damaged, such as during total body irradiation, by increasing selective pressure for adaptive oncogenic mutations. Stem Cells 2015;33:1345–1358